Association of human leukocyte antigen with interstitial lung disease in rheumatoid arthritis: a protective role for shared epitope. - Hiroshi Furukawa; Shomi Oka; Kota Shimada; Shoji Sugii; Jun Ohashi; Toshihiro Matsui; Tatsuoh Ikenaka; Hisanori Nakayama; Atsushi Hashimoto; Hirokazu Takaoka; Yoshiyuki Arinuma; Yuko Okazaki; et al. (PLoS ONE, 2012)
INTRODUCTION: Interstitial Lung Disease (ILD) is frequently associated with Rheumatoid Arthritis (RA) as one of extra-articular manifestations. Many studies for Human Leukocyte Antigen (HLA) allelic association with RA have been reported, but few have been validated in an RA subpopulation with ILD. In this study, we investigated the association of HLA class II alleles with ILD in RA. METHODS: An association study was conducted on HLA-DRB1, DQB1, and DPB1 in 450 Japanese RA patients that were or were not diagnosed with ILD, based on the findings of computed tomography images of the chest. RESULTS: Unexpectedly, HLA-DRB1*04 (corrected P [Pc] = 0.0054, odds ratio [OR] 0.57), shared epitope (SE) (P = 0.0055, OR 0.66) and DQB1*04 (Pc = 0.0036, OR 0.57) were associated with significantly decreased risk of ILD. In contrast, DRB1*16 (Pc = 0.0372, OR 15.21), DR2 serological group (DRB1*15 and *16 alleles) (P = 0.0020, OR 1.75) and DQB1*06 (Pc = 0.0333, OR 1.57, respectively) were significantly associated with risk of ILD. CONCLUSION: HLA-DRB1 SE was associated with reduced, while DR2 serological group (DRB1*15 and *16) with increased, risk for ILD in Japanese patients with RA.